The Social Ecology of Homelessness: Exploring the Dynamics of Engagement among Homeless Street Adults - Jones, Brian T. (Journal of human behavior in the social environment, 2013)
The study examines interaction patterns of homeless populations. The study explores how this population interacts within a given environment. The current study utilizes a person/environment engagement model to analyze behavioral interaction and perceptions in relation to the environment. The author establishes the notion that engagement is dependent on perception of the environment and actual environmental condition. This dual orientation presents a conundrum between internal feelings and external influence. On the one hand, behavior is a consequence of external environment. On the other hand, environment is the consequence of the individual's behavior. Given harsh conditions, the results revealed that either way of understanding is problematic. The author uses modern ecological perspective to develop conditions and interaction patterns.